Qualidade das fontes de água utilizadas nas caldas de pulverizações agrícolas do Rio Grande do Sul - Machado, Matheus Colaço (2022)
Water is the world's main natural resource. Water is a common substance with unique properties among chemical compounds, which can highlight its high melting and boiling temperature. Water resources are used for different purposes, whether in domestic, agricultural and industrial supply and in energy generation. The spraying of phytosanitary products is extremely dependent on numerous factors so that the producer can reach the desired target, which are environmental, technical and technological. Among some factors, water quality can be one of the main determinants of the success of the application. The presence of substances dissolved in water (gases, liquids or solids) varies according to the source of water and place of collection, even having a simple structure, where they may or may not affect the action of a phytosanitary product. Therefore, the objective of this work was to verify the different sources of water used in the spraying of pesticides and to evaluate the main chemical parameters, such as pH, hardness and electrical conductivity of the water intended for this purpose. 150 water samples from different mesoregions of the state of Rio Grande do Sul were collected and analyzed. In general, the analyzed water has characteristics suitable to those desired for the use of pesticides. It is extremely important to consider the conditions of the water used for the efficient and rational use of phytosanitary products.